A spatial dynamics chorematic grid to explain territories evolution Un conjunto de coremas de dinámica espacial para explicar la evolución territorial - Enault, Laure Casanova; Chatel, Cathy [UNESP] (OpenEdition, 2017)
Using the evolution of urban spaces, this paper surveys and investigates a grid of “chorèmes” (elementary graphic structures) developed for the modelling of spatial dynamics (two case studies are presented). These dynamics span the transition from France's 2010 status to its projected 2030 status, as studied in the three scenarios presented by the Ministry of Ecology, Sustainable Development and Energy's program: Sustainable Territory 2030. The article discusses the needs for modelling prospective dynamics.
Une grille chorématique des dynamiques spatiales pour expliquer l'évolution des territoires
Keywords: Choreme; Dynamic of change; Prospective; Spatio-temporal structure